Big Three Dragons: A z = 7.15 Lyman-break galaxy detected in [O iii] 88 μm, [C ii] 158 μm, and dust continuum with ALMA. (17th June 2019) - Hashimoto, Takuya; Inoue, Akio K; Mawatari, Ken; Tamura, Yoichi; Matsuo, Hiroshi; Furusawa, Hisanori; Harikane, Yuichi; Shibuya, Takatoshi; Knudsen, Kirsten K; Kohno, Kotaro; Ono, Yoshiaki; Zackrisson, Erik; et al.
Abstract: We present new ALMA observations and physical properties of a Lyman break galaxy at z = 7.15. Our target, B14-65666, has a bright ultra-violet (UV) absolute magnitude, M UV ≈ −22.4, and has been spectroscopically identified in Lyα with a small rest-frame equivalent width of ≈4 Å. A previous Hubble Space TElescope (HST) image has shown that the target is composed of two spatially separated clumps in the rest-frame UV. With ALMA, we have newly detected spatially resolved [O iii ] 88 μm, [C ii ] 158 μm, and their underlying dust continuum emission. In the whole system of B14-65666, the [O iii ] and [C ii ] lines have consistent redshifts of 7.1520 ± 0.0003, and the [O iii ] luminosity, (34.4 ± 4.1) × 10 8 L ⊙, is about three times higher than the [C ii ] luminosity, (11.0 ± 1.4) × 10 8 L ⊙ . With our two continuum flux densities, the dust temperature is constrained to be T d ≈ 50–60 K under the assumption of a dust emissivity index of βd = 2.0–1.5, leading to a large total infrared luminosity of L TIR ≈ 1 × 10 12 L ⊙ . Owing to our high spatial resolution data, we show that the [O iii ] and [C ii ] emission can be spatially decomposed into two clumps associated with the two rest-frame UV clumps whose spectra are kinematically separated by ≈200 km s −1 . We also find these two clumps have comparable UV, infrared, [O iii ], and [C ii ] luminosities. Based on these results, we argue that B14-65666 is a starburst galaxy induced by a major merger. The merger interpretation is also supported by the large specific star formation rate (defined as the star formation rate per unit stellar mass), sSFR = 260^+119_-57\: Gyr −1, inferred from our SED fitting. Probably, a strong UV radiation field caused by intense star formation contributes to its high dust temperature and the [O iii ]-to-[C ii ] luminosity ratio.